Adipocytic cells cultured from marrow have osteogenic potential. - Bennett, J; Joyner, C; Triffitt, J; Owen, M (1991)
Stromal colonies with fibroblastic morphology grown from rabbit marrow cells in culture supplemented with foetal calf serum. In this study the same marrow cells cultured with autologous rabbit plasma and hydrocortisone form colonies of a single lineage that express the adipocytic phenotype. A comparison of the potential for differentiation of cloned cell populations grown from fibroblastic and adipocytic colonies has been made using an in vivo diffusion chamber assay. The adipocytic colonies differentiated and grew to a limited size in medium with rabbit plasma and hydrocortisone, but attempts to isolate them and expand them in this medium failed. When the serum supplement was changed to foetal calf serum at day 10 the cells in the adipocytic colonies acquired a less differentiated morphology, there was a large increase in colony growth and cells were produced in sufficient numbers for the diffusion chamber assay. Thirty one fibroblastic colonies and twenty one adipocytic colonies were isolated either by limiting dilution or ring cloning and then expanded. Of these, eleven fibroblastic and eight adipocytic colonies provided enough cells (2 x 10(5) to 2 x 10(6] for implantation and culture in the chambers. Four of the eleven fibroblastic and three of the eight adipocytic colonies formed an osteogenic tissue in the chambers. It was concluded that cells that have differentiated in an adipocytic direction are able to revert to a more proliferative stage and subsequently to differentiate along the osteogenic pathway. Adipocytic and fibroblastic cells cultured in vitro from marrow have, with osteogenic cells, a common precursor in adult marrow.